Istana Maziah, Rumah Cik Teh dan Rumah Tg Nik / Jimas Chik - Chik, Jimas (Faculty of Architecture, Planning and Surveying, 1982)
Traditional Malay Architecture is diversified innstyle although the basic construction is similar throughout the Malay Peninsular Old Trengganu houses portray a distinct style of its own. Many of the traditional houses around Pulau Kambing were destroyed due to the bombings during the Japanese Occupation.. The old Istana houses built in the early 19th century had perished during the most devastating fire in the history of Trengganu in 1882. Thus almost all direct evidence of earlier Malay Architecture there were swept away in posterity. In the effort to study the architectural technology of the past a historical research and measured draining operation had been made of the last few 19th century houses left in the compound of Istana Maziah ( Many of the houses were demolished renovated or removed from the site ). The aim is to recapture the image of the whole site as it once stood and to produce drawings of Rumah Cik Teh and Tengku Nik to present the architectural skills which had established the reputation of Trengganu carpenters to be included as one of the Malay master builders in the Malay Peninsular.